Shrinking Lung Syndrome – A rare cause of recurrent dyspnoea in SLE / Hazlyna Baharuddin … [et al.] - Baharuddin, Hazlyna; Mohd Zim, Mohd Arif; Rosman, Azmillah; Mohd Zain, Mollyza (Universiti Teknologi MARA Cawangan Selangor, 2017)
Here we present a 24-year-old lady with systemic lupus erythematosus (SLE) whom we diagnosed with shrinking lung syndrome (SLS), a rare manifestation of SLE. The initial SLE manifestation was alopecia, thrombocytopenia, serositis and vasculitis. Anti-nuclear antibody (ANA), anti-double stranded DNA (dsDNA) antibody, anti-ribonucleic (RNP) and anti-Ro antibody were positive. A year after diagnosis, she started to develop intermittent dyspnea and was hospitalised on three occasions. Lung examinations revealed reduced breath sounds at both bases and dullness at the right base. Multiple chest radiographs showed bilateral raised hemi-diaphragms. Other investigations including CT pulmonary angiogram, high resolution CT of the thorax, ventilation-perfusion scan and echocardiogram were not significant. On the third hospital admission, we noticed bilateral small lung volumes in the previous high resolution CT scan. Inspiratory and expiratory chest radiographs were performed and showed minimal change in lung volumes and a diagnosis of shrinking lung syndrome (SLS) was made. Her SLE remained active with lupus nephritis despite multiple immunosuppression and she passed away two years later due to sepsis with multi-organ failure.